Tour operator perspectives on responsible tourism practices: a case of Kinabalu National Park, Sabah - Chan, Jennifer Kim Lian; Tay Kai Xin (2016)
Purpose: The purpose of this paper is to identify the key motivators triggering tour operators to practise responsible tourism in Kinabalu Park. Design/methodology/approach: Inductive and phenomenological research data were collected via in-depth interviews with 25 tour operators guiding tours in Kinabalu Park, Kota Kinabalu, Sabah. Findings: The paper uses push and pull motivation theory to explain motivation in practising responsible tourism. The findings show that push factors are more significant to tour operators as compared to pull factors. The key motivation of tour operators to practise responsible tourism is organisational benefits and own initiative (intrinsic) and response demand and market trends (extrinsic). However, the findings show that although tour operators have a positive attitude towards responsible tourism, it does not show in their tour operations of Kinabalu Park. This is because the challenges like lack stakeholders participation and low responsible tourism awareness were negatively affecting to what tour operators would like to do and what actually gets done. Practical implications: Identified motives, practices, issues and challenges are valuable information and to enhance the practices of responsible tourism in Kinabalu Park, Sabah. Originality/value: The paper provides in-depth insight of the motivation to practise responsible tourism from tour operators’ perspectives in Kinabalu Park. The finding is benefiting the implementation of responsible tourism in Kinabalu Park